IPARD funds in the function of the development of the rural areas of The Republic of Serbia - Stanislav Zekic; Bojan Matkovski; Zana Kleut (Economic Horizons, 2016)
By acquiring the conditions for the usage of the pre-accession funds of the European Union, concretely the instrument for rural development (Instrument for Pre-accession Assistance in Rural Development - IPARD), The Republic of Serbia (RS) will have a chance to improve the position of its agricultural farms and the conditions of its rural areas. Agriculture is specifically important for the economy in RS, and the rural population makes up almost one-half of the population, which additionally enlarges an interest in these funds. In addition, the objective of the research is to identify the effects of the usage of the IPARD funds on the development of the rural areas, respectively the socio-economic progress of the rural population. A qualitative descriptive analysis on the basis of the empirical data was used. The basic conclusions are that, thus, structured funds will have a limited impact on the reduction in the development inequalities and the achievement of the parity living conditions between the rural and the urban areas. Namely, the dominant focus of the IPARD funds on the investments in agricultural farms and enterprises, and not in rural households, limits the level of their impact on the rural development in RS.